Susceptibility of Biomphalaria tenagophila and Biomphalaria straminea to Schistosoma mansoni infection detected by low stringency polymerase chain reaction - JANNOTTI-PASSOS Liana Konovaloff; SOUZA Cecilia Pereira de (Universidade de São Paulo (USP), 2000)
In order to determine Schistosoma mansoni infection rates in Biomphalaria tenagophila and B. straminea, low stringency polymerase chain reaction (LS-PCR) technique was used as a complementary method to light exposure technique. LS-PCR has already been standardized in our laboratory to detect the trematode DNA in B. glabrata. Higher S. mansoni infection rates were detected using conventional method and LS-PCR. The parasite DNA profile was detected in both species after 7-day exposure to miracidia, using LS-PCR. This technique enables early detection of schistosomiasis transmission focuses, in endemic areas, before the beginning of cercariae shedding.